Farming Change: Growing more food with a changing resource base - Caribbean Regional Agricultural Policy Network; Technical Centre for Agricultural and Rural Cooperation; Inter-American Institute for Cooperation on Agriculture (CTA / CARAPN / IICA, 2012)
This publication seeks to provoke thought on the question of whether farming in the Caribbean will be able to take advantage of climate change and the changing natural environment to provide sustainable environmental, social and economic benefits for all. Part of the critical issues, perspectives and options (CIPO) series of publications, the book comprises three inter-related papers on: growing food crops without soil; forest cover (ecosystem services for sustainable farming); and combatting the invasive alien species (IAS) threat.